Possible role of α-mannosidase and β-galactosidase in larynx cancer - Olszewska, Ewa; Borzym-Kluczyk, Malgorzata; Rzewnicki, Ireneusz; Wojtowicz, Jerzy; Rogowski, Marek; Pietruski, Jan Krzysztof; Czajkowska, Aneta; Sieskiewicz, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2012)
Background : Lysosomal exoglycosidases, such as α-mannosidases (MAN) and β-galactosidases (GAL), are found in different glycoside hydrolase sequence-based families. Considerable research has proved plays the role of MAN, which play a key role in the modification and diversification of hybrid N-glycans, processes with strong cellular links to cancer. Therefore the study aim was to investigate the activities of MAN and GAL in larynx cancer compared to controls. Material and methods : Larynx cancer (n = 21) and normal healthy tissue (n = 21) were collected from patients during total laryngectomy. A biopsy of macroscopically healthy tissue in the area of the lower 1/3 of omohyoid muscle was taken for frozen sections in each case and these served as controls. The release of p-nitrophenol from p-nitrophenol derivatives of MAN and GAL was used. Results : In all specimens we observed significantly higher activity of investigated enzymes in larynx cancer compared with controls. The mean release of MAN from activated cells was 3.702 ±1.3245 nkat/g wet tissue compared to controls (1.614 ±0.8220 nkat/g wet tissue). The mean release of GAL from the activated cells was 3.383 ±2.1980 nkat/g wet tissue compared to controls (2.137 ±1.3685 nkat/g wet tissue). Differences in observed activity were statistically significant. Conclusion : The present data indicate that MAN and GAL are significantly and consistently elevated in larynx cancer growth. It also means that catabolic reactions involving glycoproteins, glycolipids and proteoglycans may play a role in larynx cancer. Further research should also evaluate the relative importance of these particular exoglycosidases in indicating the progress of the disease in considering the spectrum of identified marker mediators.